2021
DOI: 10.1177/0961203321995242
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of IgG subclass anti-nuclear antibodies (ANAs) in systemic lupus erythematosus

Abstract: Objectives Our study purpose was to detect the distribution of anti-nuclear antibody (ANA) IgG subclasses in patients with systemic lupus erythematosus (SLE) and to evaluate their influence on the inflammatory process in SLE. Methods We determined the serum levels of ANA IgG subclasses from 70 SLE patients, 25 patients with other autoimmune diseases (OAD), and 25 healthy controls using ELISA. The serum level of total ANA IgG and the avidity of ANA IgG, dsDNA IgG, and dsDNA IgG subclasses were analysed by ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Autoreactive antibody titers in autoimmune disease patients are known to fluctuate [ 32 , 33 ] and their isotypes are altered as the disease progresses. For example, isotype changes to IgG4 without the ability of complement activation and antibody‐dependent cell cytotoxicity could reduce disease progression [ 34 , 35 , 36 ]. Therefore, there are attempts to use it as a prognostic biomarker [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoreactive antibody titers in autoimmune disease patients are known to fluctuate [ 32 , 33 ] and their isotypes are altered as the disease progresses. For example, isotype changes to IgG4 without the ability of complement activation and antibody‐dependent cell cytotoxicity could reduce disease progression [ 34 , 35 , 36 ]. Therefore, there are attempts to use it as a prognostic biomarker [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant anti-nuclear IgG4 antibody titers (ANA-IgG4) have been detected in SLE patients, and it has been suggested that the effect of these antibodies on complement consumption and the production of proinflammatory cytokines may play a role in inhibiting the progression of SLE. The presence of anti-dsDNA IgG4 antibodies was also reported and was associated with skin lesions and kidney involvement in patients with SLE ( 74 ). Pan et al.…”
Section: Other Rheumatic Diseases and Igg4mentioning
confidence: 94%
“…The role of IgG4 in helmints infection is still analyzed. Essentially, two possible mechanisms are proposed that can lead to the inhibition of IgE-mediated immunity and resistance to helmints ( 74 , 76 ). One is associated with the inhibition of a switch in plasma cell production from IgM via IgG4 to IgE.…”
Section: Other Rheumatic Diseases and Igg4mentioning
confidence: 99%
“…[62,63] Anti-dsDNA IgG4 antibodies were detected and found to be linked with cutaneous manifestations and renal impairment in individuals diagnosed with SLE. [64] Diverse findings could arise from varying disease stages and methodologies employed across disparate research facilities. However, each of these studies demonstrated the participation of IgG4 in certain traditional non-IgG4-RD conditions.…”
Section: Igg4 In Slementioning
confidence: 99%